Relationship between oxidative stress parameters and asymptomatic organ damage in hypertensive patients without diabetes mellitus. (October 2015) - Ates, Ihsan; Ozkayar, Nihal; Topcuoglu, Canan; Dede, Fatih
Abstract Objective. We aimed to evaluate the levels of oxidative stress (OS) parameters such as total antioxidant status or TAS, total oxidant status (TOS), OS index (OSI), paraoxonase 1 (PON1), arylesterase, and total thiol in hypertensive patients with and without asymptomatic organ damage (AOD), and to determine the relationship between these parameters and AOD. Design. Sixty-six patients (21 men, 45 women) with AOD and 66 patients without AOD (21 men, 45 women) were enrolled in the study. Serum OS parameters were measured by colorimetric method. Results. The OSI levels were found to be higher while PON1, PON1/high-density lipoprotein, and arylesterase levels were found to be lower in patients with AOD compared with those in the patients without AOD. Stepwise regression analysis showed high 24-h mean systolic blood pressure, OSI, and low arylesterase level to be independent predictors of AOD. Conclusion. OS level was found to be higher in hypertensive patients with AOD compared with the patients without AOD. However, it is not clear whether increased OS leads to AOD or AOD increases the level of OS. For this purpose, OS level needs to be decreased by antioxidant therapies and patients need to be followed up for a longer duration.